Deep Brain Stimulation at Variable Frequency to Improve Motor Outcomes in Parkinson's Disease. Issue 5 (1st October 2018) - Jia, Fumin; Wagle Shukla, Aparna; Hu, Wei; Almeida, Leonardo; Holanda, Vanessa; Zhang, Jianguo; Meng, Fangang; Okun, Michael S.; Li, Luming
ABSTRACT: Introduction: Deep brain stimulation (DBS) with high frequency (HFS) is a well‐established therapy for Parkinson's disease (PD); however, low frequency DBS (LFS) may control axial symptoms including freezing of gait (FOG). We conducted a pilot safety and feasibility study to examine if a novel DBS paradigm of variable frequency stimulation (VFS) that combined HFS and LFS would capture a broader set of motor symptoms. Methods: Four PD patients with bilateral STN DBS and FOG were enrolled. A UPDRS III and 10 m timed up and go (TUG) task were performed off medications‐off DBS and then one hour after HFS and one hour after VFS programming. Results: The UPDRS III motor score improved by additional 14% during VFS setting when compared to HFS. VFS also increased gait speed (mean change 45%) and reduced the number of freezing episodes (mean change 58%). Conclusions: VFS improves UPDRS and FOG in PD when compared to HFS.Copyright © 2018 International Parkinson and Movement Disorder Society Abstract : View Supplementary Video 1